(Auto)percepcja tożsamości w ujęciu współczesnej młodzieży na podstawie Oblicza Szymona Kołody - Judzińska, Aneta (Kultura-Społeczeństwo-Edukacja, 2018)
The author, by taking into account popular and scientific discourse about “liquid”, “globalized” identity (viewed in the context of various social and family roles), attempts to reconstruct an image of a contemporary teenager’s identity, referring to “The Face”, a 2-minute impression by seventeen year old Szymon Kołoda. On this basis she shows areas of participation of contemporary young people, who balance between two realities: the real and the virtual one. The author supports her reasoning with the concept of hybrid identity by Zygmunt Bauman and the global teenager / culture of diffusion by Zbyszko Melosik. The aim of this article is to make a subjective, socio-psychological interpretation of identity creations present in Szymon Kołoda’s picture, rather than psychological diagnosis of the teenage actor’s “inner integrity”.